2016
DOI: 10.1007/s00330-016-4208-7
|View full text |Cite
|
Sign up to set email alerts
|

Regional thermochemotherapy versus hepatic arterial infusion chemotherapy for palliative treatment of advanced hilar cholangiocarcinoma: a retrospective controlled study

Abstract: • Regional TCT is a novel combination for palliative treatment of advanced HC • Our data showed significantly promising outcomes in the TCT group • HC patients with metal stenting appeared to derive greater benefit from TCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Median OS (11.5, 95% CI: 7.7, 14.3) in the DEB-TACE group was similar to those found in previous studies ( Kim et al, 2008 ; Zhou et al, 2020 ) but was longer than that of the C-TACE group in this study. Several studies of second-line chemotherapy for advanced biliary tract cancer showed that median OS was less than 8 months, and hepatic arterial infusion chemotherapy for advanced cholangiocarcinoma showed median OS was 13.2 months ( Chen et al, 2016 ; Lamarca et al, 2021 ; Huang et al, 2022 ). The OS of these studies are similar to ours (median OS in DEB-TACE group: 11.5 months).…”
Section: Discussionmentioning
confidence: 99%
“…Median OS (11.5, 95% CI: 7.7, 14.3) in the DEB-TACE group was similar to those found in previous studies ( Kim et al, 2008 ; Zhou et al, 2020 ) but was longer than that of the C-TACE group in this study. Several studies of second-line chemotherapy for advanced biliary tract cancer showed that median OS was less than 8 months, and hepatic arterial infusion chemotherapy for advanced cholangiocarcinoma showed median OS was 13.2 months ( Chen et al, 2016 ; Lamarca et al, 2021 ; Huang et al, 2022 ). The OS of these studies are similar to ours (median OS in DEB-TACE group: 11.5 months).…”
Section: Discussionmentioning
confidence: 99%
“…Regional hyperthermia, in comparison, does not require sedation and only takes 30-60 min. Common adverse events related to regional hyperthermia and mEHT during the procedure are thermal stress, local discomfort, hot sensation, abdominal and back pain, bolus pressure, position-related discomfort or pain, tachycardia, and grade I and II burns at the heated region[ 29 - 46 ]. Increased liver enzymes, skin rashes at the heated region, and occasional mild subcutaneous fat necrosis, nausea, dyspnea, and urinary urgency can also occur after the procedure[ 29 , 39 - 46 ].…”
Section: Hyperthermia In Cancer Treatmentmentioning
confidence: 99%
“…Common adverse events related to regional hyperthermia and mEHT during the procedure are thermal stress, local discomfort, hot sensation, abdominal and back pain, bolus pressure, position-related discomfort or pain, tachycardia, and grade I and II burns at the heated region[ 29 - 46 ]. Increased liver enzymes, skin rashes at the heated region, and occasional mild subcutaneous fat necrosis, nausea, dyspnea, and urinary urgency can also occur after the procedure[ 29 , 39 - 46 ]. Several studies have reported a higher incidence of hematotoxicity in patients treated with hyperthermia than in those without hyperthermia[ 30 , 31 , 47 ], possibly associated with the increased cytotoxicity of chemotherapeutic agents in hyperthermia[ 13 , 15 , 18 ].…”
Section: Hyperthermia In Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation